2019
DOI: 10.1002/mds.27723
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral mitochondrial function correlates with clinical severity in idiopathic Parkinson's disease

Abstract: Background Parkinson's disease is an intractable disorder with heterogeneous clinical presentation that may reflect different underlying pathogenic mechanisms. Surrogate indicators of pathogenic processes correlating with clinical measures may assist in better patient stratification. Mitochondrial function, which is impaired in and central to PD pathogenesis, may represent one such surrogate indicator. Methods Mitochondrial function was assessed by respirometry experiment in fibroblasts derived from idiopathic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 42 publications
(82 reference statements)
4
39
1
Order By: Relevance
“…This metabolic phenotype could potentially represent a biomarker that can stratify and define a specific subset of sAD patients that might then respond to a personalised therapeutic approach. Previous research has shown that the metabolic profile identified in fibroblasts from sporadic Parkinson's disease patients differs from that identified here in fibroblasts from sAD [46,47].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This metabolic phenotype could potentially represent a biomarker that can stratify and define a specific subset of sAD patients that might then respond to a personalised therapeutic approach. Previous research has shown that the metabolic profile identified in fibroblasts from sporadic Parkinson's disease patients differs from that identified here in fibroblasts from sAD [46,47].…”
Section: Discussioncontrasting
confidence: 72%
“…This is not the first study, however, to show that the metabolism of peripheral cells outside the nervous system is affected in sAD. White blood cells [55], platelets [56] and fibroblasts have been shown to have metabolic abnormalities in multiple studies [46,47,57,58]. Identifying that fibroblast mitochondrial abnormalities correlate with neuropsychological markers of AD opens up avenues to use fibroblast metabolic parameters as biomarkers of sAD, and also as a high throughput drug screening model, as well as potential outcome measures of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived fibroblasts have become a popular model for Parkinson’s research; they have been utilised in mechanistic and drug screening studies. However, it is proposed that fibroblasts must be cultured in glucose-free media to study mitochondrial dysfunction [ 59 , 60 , 61 , 62 ] in PD. Fibroblasts cultured in glucose media have a net ATP production via glycolysis and oxidative phosphorylation.…”
Section: Glycolytic Changes In Parkinson’s Diseasementioning
confidence: 99%
“…Fibroblasts cultured in glucose media have a net ATP production via glycolysis and oxidative phosphorylation. Whereas fibroblasts cultured in media containing galactose alone do not have a net production of ATP from glycolysis, unmasking aberrations in mitochondrial function [ 59 ]. This suggests that glycolysis may play a protective role in PD pathology, and like in AD, compensates for abnormal mitochondrial function.…”
Section: Glycolytic Changes In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation